Bond-based peridynamic model for tensile deformation and fracture of polycarbonate and polypropylene - Azizi, Muhammad Azim; Azman, Muhammad Amin; Norazak, Muhammad Farhan Aqil; Fauzi, Muhammad Amirul Hakim (Trans Tech Publications, 2024)
Fracture mechanics has been a crucial aspect in the field of engineering science as technologies are rapidly growing nowadays. Various numerical methods have been developed to. Meanwhile, used of materials types different behaviour in fracture analyze in industries. The application of polymers garners attention worldwide due to outstanding characteristics such as good strength, lightweight, and high temperature resistance, exemplified by polymers like polycarbonate (PC) and must aspects failure such Hence, (PP). polypropylene of materials into consideration when conditions arise that may lead to failure, such as high-load impact, fatigue, and extreme taken be Peridynamic bond-based study, a temperatures. In this model (PD) for the tensile behaviour, including fracture, of polymers has been developed. The PD model is constructed using the Centos and software and encompasses both brittle ductile fracture behaviours. Numerical results, including crack propagation, damage zone, and force-extension curves of notched specimens, are validated by comparison with experimental results of PC and PP. Through the validation process, PC specimens exhibit a difference percentage range for maximum load and a difference percentage range for maximum load and rupture extension of 31.2% to 43.5% and 0.9% to 30%, respectively. Consequently, specimens respectively. PP to 4.6%, and 2.4% to 18.8% 2.9%extension of show rupture for the brittle validation results indicate that the PD model specimens aligns more closely with experimental data compared to the PD model for ductile specimens.